2020
DOI: 10.1017/s1751731119003434
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of functional longevity in five rabbit lines

Abstract: The objectives of this study were to analyse the differences in the genetic determination of functional longevity in five Spanish lines of rabbits and to check how different systematic factors might affect this genetic determination. Four of the lines were maternal (lines A, V, H and LP), these lines were established selecting base generation animals according to different criteria, but in the subsequent generations all of them were selected for litter size at weaning. The other is the paternal line R, this li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 21 publications
4
24
0
Order By: Relevance
“…This result was in accordance with previous reports by EL Nagar et al. (2020) who stated that the L rabbit line had a longer functional longevity than the A, V, H and R rabbit lines. Also, Theilgaard et al.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This result was in accordance with previous reports by EL Nagar et al. (2020) who stated that the L rabbit line had a longer functional longevity than the A, V, H and R rabbit lines. Also, Theilgaard et al.…”
Section: Discussionsupporting
confidence: 94%
“…In this regard, however, El Nagar et al. (2020) showed that, in a single farm, with the same purebred lines as were used in this study, they followed a similar lifetime risk pattern. This risk decreased as the order of positive palpation increased.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The economic weight of doe replacement rate as an estimation of the economic weight of longevity is relatively low (−0.29 €/percentage unit) compared with other traits like, for example, efficiency in the use of feed or prolificacy (Cartuche et al., 2014). However, until now, in the computation of this weight, some relevant factors associated with management, welfare and ethics are not properly defined in the farm benefit function (EL Nagar et al., 2020). With the aim of creating a maternal line outstanding for its longevity, Sánchez et al.…”
Section: Introductionmentioning
confidence: 99%